Electromagnetic Vector Sensor array parameter estimation method - Lanxiang Zhu; Yaowu Shi; Yiran Shi; Life Deng; Hongwei Shi (Institute of Advanced Engineering and Science, 2013)
Joint estimation method for DOA and polarization parameters of single electromagnetic vector sensor is mostly concerned in radar signal processing now. This paper presents a new algorithm which uses the cyclostationary property of signal. It gets the estimation of DOA and polarization parameters from the noise subspace with minimum norm method. This method can reduce the estimate error of noise subspace vector. At the same time, it is immune to the additional stationary noise of any distribution and interference signals with different cyclic frequencies. Method has been tested by computer simulation and the test result is show in the paper. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2562